Treatment of Class III Malocclusion: Atypical Extraction Protocol - Fernando Pedrin Carvalho Ferreira; Maiara da Silva Goulart; Renata Rodrigues de Almeida-Pedrin; Ana Claudia de Castro Ferreira Conti; Maurício de Almeida Cardoso (Case Reports in Dentistry)
The treatment of Angle Class III malocclusion is rather challenging, because the patient’s growth pattern determines the success of long-term treatment. Early diagnosis and treatment are still highly discussed issues in orthodontic literature. This type of early intervention has been indicated more frequently in order to eliminate primary etiological factors and prevent an already present malocclusion from becoming severe. However, when a patient is diagnosed in adulthood, manipulation of the bone bases becomes extremely limited, as there is no longer any potential for growth. Treatments are restricted to dental compensations when possible or orthognathic surgery. However, owing to the high cost and inherent risk of the surgical procedure, this treatment option is often denied by the patient; in such a case, the orthodontist has little choice but to perform, where possible, compensatory treatments to restore a functional occlusion and improve facial esthetics. This article reports a case of Class III malocclusion in a patient who opted for compensatory treatment with lower molar extraction that allowed for correction of the midline and the overjet. Good facial esthetics and functional normal occlusion were achieved at the end of the treatment.